Moderate Islamic Movement in the Midst of the Plurality of Indonesian Society - Iswahyudi Iswahyudi (Budapest International Research and Critics University, 2023)
The use of the term modernist Islam is to denote any activist, organization, or party that seeks to establish an Islamic state or to comprehensively reorganize Indonesian society according to Islamic values. In contrast, the term conservative Islam is used to denote a broader category of activists, organizations, and parties seeking to preserve, expand, introduce, or codify traditional Islamic practices as law or the application of sharia in a more stringent, situational or symbolic fashion. Islamists, in this sense, are by definition conservatives, although conservatives need not be Islamists. It should also be noted that Islamism is more narrowly defined as a specific revolutionary movement to replace westernized postcolonial states with authentic Islamic institutions and anything less comprehensive than those under the umbrella of Islamic conservatism or neoconservatism. This paper explores the various manifestations of pressure on religious pluralism in post-transitional Indonesia. Democratization, decentralization, and socio-cultural Islamization do not strengthen or dismantle the system of religious pluralism in Indonesia. Instead, they generate sharp and growing disparities in how pluralism is institutionalized and practiced: disparities across regions, localities, and groups.